Back to the cellar. Underground urban spaces of fear and air warfare in Berlin, 1940-1945. - Kalff, Sabine (Deutsches Institut für Urbanistik, 2020)
As a consequence of air raids, a substantial part of Berlin's population resided permanently in cellars towards the end of World War II. Berliners thus returned to the space that around 1900 constituted an important dwelling place for the urban poor. Based on war diaries and prose, this essay examines the reorganization of the vertical under the influence of the air war, particularly within the apartment building. The large-scale destruction of urban housing and the return of the population to the cellar are understood as indicative of a psychological, social, and political reversal.

Der Beitrag widmet sich den Berliner Wohnhäusern, die während des Zweiten Weltkrieges zu Räumen der Angst wurden. Besondere Aufmerksamkeit gilt der vertikalen Perspektive, um zu verstehen, wie Kellerräume in ihrer Ambivalenz zwischen Schutz- und Angstraum und nicht zuletzt in Bezug auf die soziale Kontrolle fungierten. Die Beobachtungen der Autorin basieren auf einer Auseinandersetzung mit den Vorkriegskontexten, als die Vertikalität einer Mietskaserne die soziale Schichtung widerspiegelte.
Keywords: Bombardierung; Zweiter Weltkrieg; Wohnhaus; Mietskaserne; Bewohner; Angst; Keller; Bunker; Sozialbeziehung; Sozialschicht; Notunterkunft; Psychologie